Building a deductive reasoning test according to the latent trait’s theory using the Rush model for university students - Bilal, Jian Yahya; Alwan, Abbas (Al-Adab Journal, 2021)
The current research aims to build inferential thinking according to the theory of latent traits, using the Rush model among university students. To achieve this goal, the researcher followed the scientific steps in building the test, starting specifically with the theoretical concept of inferential thinking according to Thurston’s theory, taking into account the accuracy and comprehensiveness of all ideas in the test, and the researcher took the modifications that were made to the paragraphs when they were presented to experts in the Department of Educational and Psychological Sciences. The test was applied to a sample of (400) male and female students from (official universities / morning shift in Wasit city) who were chosen by the random sample method, and the researcher relied on the single-teacher Rush model, which is one of the models of the theory of latent features to analyze the test items, and to verify Model Assumptions The researcher follows the following: 1- One-dimensional: To verify this assumption, the researcher conducted a factor analysis to test inferential thinking by the method of basic components. 2- Matching the paragraphs of the model based on the value of the square (χ2) for good conformity according to the program outputs, a statistically significant level of significance (0.05). 3- The value of the discriminant factor for the test approached (1)، as its value reached (0.569) 4- The independence of measurement to achieve the objectivity of measurement, as represented by the Rush model, and none of the paragraphs were excluded. 5- In order to get rid of fractures and negative signals about the researcher, the log unit for estimating the difficulty of the paragraphs, and for estimating the ability of individuals and their standard errors to the unit of WAT. In light of the results of the current research, the researcher came to some conclusions, recommendations and suggestions